Fetal pharyngeal glial heterotopia manifested as polyhydramnios: a rare case with difficult prenatal diagnosis - Xiaoting Ke; Huaijie Cai; Wei Wang; Qingquan Lai (BMC, 2023)
Abstract Background Glial heterotopia is a rare congenital developmental malformation that presents as tumor-like lesions of the nerve tissue that grow outside the nervous system, but are not true tumors. At present, most cases are reported in neonates and children and are very rarely found in fetuses. The present report describes a case of fetal pharyngeal glial heterotopia and associated imaging findings to better understand the disease in the future. Case presentation A 32-year-old pregnant woman was admitted to the hospital with polyhydramnios. An ultrasound examination revealed a hypoechoic mass in the neck of the fetus. Magnetic resonance imaging showed a well-defined mass with significant compression of the esophagus and airway. The amniotic fluid index was approximately 40 cm. Considering that difficulty swallowing and breathing may occur due to compression by the mass after birth, tracheotomy and mass resection should be performed immediately. The difficulty of the tumor resection procedure and the nature of the tumor are both factors affecting the prognosis of the fetus. The pregnant woman eventually chose to induce labor. The fetal pharyngeal mass was then resected and its pathological examination indicated pharyngeal glial heterotopia. Conclusions Polyhydramnios due to pharyngeal glial heterotopia is extremely rare and accurate prenatal diagnosis is challenging. Clinical diagnosis of glial heterotopia in preterm fetuses is difficult. Therefore, understanding glial heterotopia is helpful to improve clinical treatment options.